MicroRNAs in myeloproliferative neoplasms. (25th February 2013) - Zhan, Huichun; Cardozo, Christopher; Raza, Azra
Summary: The chronic myeloproliferative neoplasms (MPN), including polycythaemia vera (PV), essential thrombocythaemia (ET) and primary myelofibrosis (PMF), are clonal stem cell disorders characterized by dysregulated haematopoietic stem cell expansion and production of red cells, white cells and platelets alone or in combination. An acquired mutation JAK2 V617F can be found in all three disorders and shows many of the phenotypic abnormalities of the diseases in murine models. The disease phenotype is also influenced by other unknown genetic or epigenetic factors. MicroRNAs (miRNA) are 18–24 nucleotide single‐stranded non‐protein‐coding RNAs that function primarily as gene repressors by binding to their target messenger RNAs. There is growing evidence that miRNAs regulate haematopoiesis in both haematopoietic stem cells and committed progenitor cells. Here, we review the field of miRNA biology and its regulatory roles in normal haematopoiesis with an emphasis on miRNA deregulations in MPNs. Continued research into how miRNAs impact JAK2 V617F clonal expansion, differential haematopoiesis among different MPNs, disease progression and leukaemia transformation will lead to a better understanding of the development of these disorders, their clinical manifestations, and their treatment.